Teachers’ views of the learning potential - Bitu, Barras, Geofroy, Ali, Lochan, McLeod, Stephens-James & Valentine-Lewis (Caribbean Educational Research Information Service, 2017)
One key determinant of inclusion regarding children from low-income households is belief in their learning potential. Teacher educators of the in-service post-graduate Diploma in Education programme are charged with helping teacher-participants interrogate and modify negative views they may hold of students from such backgrounds. Some views may constitute an approach inimical to the empowerment of children. While views of teacher-participants on the learning potential of children from low-income households are discussed early in the programme, there is need for systematic analysis of such views. In so doing, insights gained can guide the approach of teacher educators in their quest for sensitizing teacher-participants as to appropriate responses in educating children from low-income households. Using a qualitative case-study approach, the views of nine teacher-participants were obtained through semistructured focus group interviews that were analysed thematically using the grounded theory approach. Findings revealed that although teacher-participants expressed views acknowledging the challenging life contexts of students from low-income households, they were also keenly aware of the empowering potential of positive relationships in the educational endeavour. Practical asset-based strategies for teachers and administrators were advanced in response to issues confronting students from low-income households. Recommendations suggested ways in which teacher education could be enhanced.
Keywords: Teacher Education; Low-Income High School Students; Diploma in Education Programme